A review of leadership and capacity gaps in nutrition-sensitive agricultural policies and strategies for selected countries in sub-saharan Africa and Asia - Aryeetey, Richmond; Covic, Namukolo (SAGE Publications, 2020)
Agriculture policies and strategies designed, purposefully, to address malnutrition are considered nutrition-sensitive and are a critical component of global efforts to address malnutrition in all its forms. However, limited evidence exists on extent and how nutrition is being integrated into agriculture sector policies, strategies, and programs. A review was conducted to address 2 questions: How nutrition-sensitive are agriculture policies, plans, and investments in selected Sub-Saharan African (SSA) and Asian countries? and Which capacity and leadership gaps limit scale up of nutrition-sensitive agriculture policy and programs?The review of existing policies was conducted for 11 selected focus countries (9 in SSA and 2 from Asia) of the CGIAR (Consultative Group on International Agricultural Research) Collaborative Research Programme on Agriculture for Nutrition and Health led by the IFPRI (International Food Policy Research Institute). The Food and Agriculture Organization (FAO)’s 10-point key recommendations for designing nutrition-sensitive agricultural interventions was used as an analytical framework. Additionally, a rapid systematic review of published peer-reviewed and grey literature was carried out to identify capacity gaps based on the United Nations Development Program’s capacity assessment framework.We found that there is nutrition sensitivity of the policies and strategies but to varying degrees. There is limited capacity for optimum implementation of these policies, programs, and strategies. For most of the countries, there is capacity to articulate what needs to happen, but there are important capacity limitations to translate the given policy/program instruments into effective action.The gaps identified constitute important evidence to inform capacity strengthening of nutrition-sensitive actions for desired nutrition and health outcomes in Africa and Asia.